2020
DOI: 10.5267/j.msl.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Vitality of work involvement in mediation: The effect of organizational justice on organizational citizenship behavior

Abstract: This paper performs an investigation on Organizational Citizenship Behavior (OCB) head of the biMBA-AI-UEO unit in DKI Jakarta Province, which is a franchise brand of kindergarten schools in Jakarta. The purpose of the research, is to know and analyze: the direct influence of Organizational Justice on OCB unit head biMBA-AIUEO; the direct influence of Work Involvement on OCB; the direct influence of Organizational Justice on the Work Involvement, and the indirect effect of Organizational Justice on OCB head of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 8 publications
1
7
0
3
Order By: Relevance
“…Another study conducted in Pakistan by results was justice perceptions predicted OCBs among nurses. However, several studies confirmed the impact of OJ on OCBs Hidayah & Harnoto, 2018;Sujono et al, 2020) on the other hand. Fairness did not impact on OCBs directly (Bauwens et al, 2019).…”
Section: Hypotheses Development Oj and Ocbsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in Pakistan by results was justice perceptions predicted OCBs among nurses. However, several studies confirmed the impact of OJ on OCBs Hidayah & Harnoto, 2018;Sujono et al, 2020) on the other hand. Fairness did not impact on OCBs directly (Bauwens et al, 2019).…”
Section: Hypotheses Development Oj and Ocbsmentioning
confidence: 99%
“…OJ represents the individual interpretation of justice in the institution. It provides an insight into how decisions are taken concerning the distribution of outcomes and the sense of justice over the production (Sujono, Tunas, & R Sudiarditha, 2020). According to Bies and Moag (1986), Folger and Greenberg (1985), Greenberg (1990), and Tyler and Bies (1990), OJ consists of distributive, procedural, and interactional justice.…”
Section: Organizational Justicementioning
confidence: 99%
“…Specifically, a variety of research has been done in different commercial organizations based on the relationship between the perception of OJ and OCB ( Ali, 2016 ; Chan and Lai, 2017 ; Donglong et al., 2020 ; Lim and Loosemore, 2017 ). Following a thorough and exhaustive review of the previous literature, it was observed that, with few exceptions (see, Donglong et al., 2020 ; Sujono et al., 2020 ), little is known regarding the mechanism through which OJ can stimulate academic staff's involvement in OCB is still unexplored in the context of HEIs.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, fairness in the organization does not lead directly to OCB. Prior studies explored several intervening variables between OJ and OCB, such as organizational commitment ( Donglong et al., 2020 ; Jehanzeb and Mohanty, 2019 ), organizational trust ( Ullah et al., 2021 ), job satisfaction ( Junru and Huang, 2019 ; Khan et al., 2020 ), job involvement ( Sujono et al., 2020 ), psychological ownership ( Jnaneswar and Ranjit, 2021 ), and leader-member exchange ( Hasyim and Palupiningdyah, 2021 ; Sheeraz et al., 2020 ). However, there is still a call to uncover the “black box” remaining in the OJ—OCB relation ( Ambrose et al., 2021 ; Rana et al., 2018 ; Zayed et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Organizational justice refers as the individual interpretation of fairness in the organization. It provides an insight into how decisions are taken concerning the division of outcomes and the sense of justice over contribution (Sujono, Tunas, & Sudiarditha, 2020). Adam's work of equity theory can be considered representative and the main advancement which emphases on matters of the fairness and justice at workplace.…”
Section: Introductionmentioning
confidence: 99%